Effect of nitrogen and potassium sources on yield attributes and yield of chilli (Capsicum annuum L.) - K U Jyothi, P V Reddy, S Suryakumari, S Bharathi, (Journal of Spices and Aromatic Crops, 2015)
In a field experiment the comparative efficacy of three sources of nitrogen viz., urea, calcium ammonium nitrate and ammonium sulphate and two sources of potassium viz., muriate of potash and sulphate of potash on yield attributes and yield in chilli cv LCA 353 was evaluated. Among the treatments tested the highest number of fruits per plant and yield was recorded in the treatment where the recommended nitrogen of 300 kg ha-1 was given 50% as urea and remaining 50% as CAN and recommended potassium of 120 kg ha-1 as 50% MOP and remaining 50% as SOP (228.4 fruits plant-1 and 48.85 q ha-1). However, in the treatment where the recommended nitrogen of 300 kg ha-1 was given 50% as urea and remaining 50% as AS/CAN and recommended potassium of 120 kg ha-1 as 50% MOP and 50% SOP were economical with C:B ratio of 1:1.95 as against control with 1:1.64 where split application of recommended N and K was given in single source as urea and muriate of potash.